Correlation between Ultrasound Reflection Intensity and Tumor Ablation Ratio of Late-Stage Pancreatic Carcinoma in HIFU Therapy: Dynamic Observation on Ultrasound Reflection Intensity. (26th December 2013) - Ge, Hui-Yu; Miao, Li-Ying; Wang, Jin-Rui; Xiong, Liu-Lin; Yan, Fang; Zheng, Cui-Shan; Jia, Jian-Wen; Cui, Li-Gang; Chen, Wen
Abstract : The minimally invasive high-intensity focused ultrasound (HIFU) therapy is thermal ablation treatment for late-stage pancreatic carcinoma with widely recognized safety and effectiveness, but there are currently no instant assessment methods for its ablation effect. It is vital to find a real-time high-sensitive assessment method. This research aims to dynamically observe the variation rules of ultrasound reflection intensity, analyze the correlation between ultrasound reflection intensity and tumor ablation ratio, and find out the value of ultrasound reflection intensity in prognosis of HIFU ablation effect. HIFU intermittent therapies were retrospectively analyzed for 31 subjects with late-stage pancreatic carcinoma from March 2007 to December 2009 in the study. The variation rules of the ultrasound reflection intensity during HIFU therapy were summarized and the correlation between ultrasound reflection intensity and tumor ablation ratio was analyzed based on the tumor ablation ratio indicated by CT scanning. The conclusion is that variation of ultrasound reflection intensity can be used for initial assessment of tumor ablation in HIFU therapy and early prognosis of overall HIFU ablation, providing important clinical basis for improving safety and effectiveness of HIFU therapy. Ultrasound can work as a real-time imaging instrument for observation of HIFU ablation effect in treating late-stage pancreatic carcinoma.